Answer:
Hi
Step-by-step explanation:
the answer is :
![4 \sqrt{7} + 8 = x \\ aproximatly \: 18.58](https://tex.z-dn.net/?f=4%20%5Csqrt%7B7%7D%20%20%2B%208%20%3D%20x%20%5C%5C%20aproximatly%20%20%5C%3A%2018.58)
with phithaghoreth law you can find the base of the two triangles
and then you sum
if you need more explanation tell me
Answer:
![y = 5 {x}^{3} - 2](https://tex.z-dn.net/?f=y%20%3D%205%20%7Bx%7D%5E%7B3%7D%20%20-%202)
Step-by-step explanation:
The given differential equation is :
xy′−3y=6
We want to determine which of the following options is a solution to the differential equations.
The function that satisfies the differential equation is a solution.
We can verify that
![y = 5 {x}^{3} - 2](https://tex.z-dn.net/?f=y%20%3D%205%20%7Bx%7D%5E%7B3%7D%20%20-%202)
satisfy this differential equation.
We differentiate to get:
![y' = 15 {x}^{2}](https://tex.z-dn.net/?f=y%27%20%3D%2015%20%7Bx%7D%5E%7B2%7D%20)
We substitute the function and its derivative into the differential equation to get:
![x(15 {x}^{2}) - 3(5 {x}^{3} - 2) = 6](https://tex.z-dn.net/?f=x%2815%20%7Bx%7D%5E%7B2%7D%29%20-%203%285%20%7Bx%7D%5E%7B3%7D%20%20%20-%202%29%20%3D%206)
We expand and simplify on the left:
![15 {x}^{3}- 15 {x}^{3} + 6= 6](https://tex.z-dn.net/?f=15%20%7Bx%7D%5E%7B3%7D-%2015%20%7Bx%7D%5E%7B3%7D%20%20%20%2B%206%3D%206)
This simplifies to:
![6 = 6](https://tex.z-dn.net/?f=6%20%3D%206)
Verified.
We can show that all the other functions do not satisfy this differential equation
Answer:
m <4= 57 degrees
m<5= 123 degrees
m<6= 35 degrees
I hope this helps and good luck!
(4,3) you add 5 to the x and subtract 3 from y
2(3x - 1) ≥ 4x - 6 | Starting equation
6x - 2 ≥ 4x - 6 | Distribute the 2
2x - 2 ≥ -6 | Subtract 4x from each side
2x ≥ -4 | Add -2 to each side
x ≥ -2 | Divide both sides by 2
So, x must be greater or equal to -2 to be in the solution set.